Evaluation of comparative efficacy of Celastrus paniculatus (Jyotishmati) capsule versus sertraline capsule in the management of Chittodvega (generalized anxiety disorder): protocol for a randomized controlled trial [version 3; peer review: 2 approved, 1 approved with reservations] - Sadhana Misar; Mayank Rai; Reeya Gamne (F1000Research)
Background Generalized anxiety disorder (GAD) (Chittodvega) is one among many types of mental disorders explained in Ayurveda. It can be defined as a Chitta (mind) + Udvega (anxiety)= Chittodvega- Anxious status of a mind. Celastrus paniculatus also known as Jyotishmati stimulates and improves the digestive fire and metabolism at a cellular level (Jatharagni and Majja dhatwagni). It can be correlated to GAD. GAD is characterized by feelings of threat, restlessness, irritability, sleep disturbance, and tension, and symptoms such as palpitations, dry mouth, and sweating. It affects women more frequently than men and prevalence rates are high in midlife (prevalence in females over age 35: 10%) and older subjects. In modern medicine the first-line psychological and pharmaceutical treatments are selective serotonin reuptake inhibitors (SSRIs) like sertraline (SNRIs). Aim and objectives To evaluate the comparative efficacy of Jyotishmati versus sertraline in the management of Chittodvega. Methods In this randomized active controlled double blind equivalence trial a total of 70 patients will be enrolled and divided into two equal groups. Patients between 20–50 years age of either gender having symptoms of Chittodvega and a Hamilton anxiety rating (HAM-A) scale score less than 24 (i.e., mild to moderate) will be selected for the study. In Group A, sertraline capsules 25 mg for first 7 days and then dose increased to 50 mg at bedtime for next 53 days and in Group B Jyotishmati Capsules 500 mg will be given twice a day after food with water for 60 days. Result and observation The patients will be assessed on the HAM-A scale, serum cortisol and WHO Quality of Life on day 0, 30, 60 and 90 and data will be analyzed using paired and unpaired t-tests for continuous variables and chi-square tests for categorical variables to evaluate whether treatments are equivalent. Trial registration CTRI No. REF/2023/07/069880 Date – 15/09/2023